Adaptive multi-channel transmission power control for industrial wireless instrumentation - Ikram,W; Petersen,S; Orten,P; Thornhill,NF (IEEE Transactions on Industrial Informatics, 2014)
The adoption of wireless technology for industrial wireless instrumentation requires high-quality communication performance. The use of transmission power control (TPC) can help address industrial issues concerning energy consumption, interference, and fading. This paper presents a TPC algorithm designed for industrial applications based on theoretical and empirical studies. It is shown that the proposed algorithm adapts to variations in link quality, and is hardware-independent and practical.